Analisis Kesulitan Mahasiswa Dalam Menyelesaikan Soal Struktur Aljabar Ring Materi Field - Azzuhro Azzuhro; Farah Mutia Putri; Assyifa Alfianda; Chintia Paramita Tarigan; Astuti Handayani; Siti Maysarah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Ring Algebraic Structure is one of the subjects in the Mathematics Education Study Program. This ring algebra course generally has a goal in terms of building students' algebraic thinking and reasoning abilities, but when viewed from the point of view of the learning process students often experience difficulties. The purpose of the research conducted by these researchers was to describe and identify students' difficulties in facing and solving problems regarding ring algebraic structures, especially in field material. Researchers used sixth semester students of the PMM Study Program at UINSU as the subjects of this study. Researchers used descriptive research with a qualitative approach that used data collection techniques in the form of; tests, documentation, and interviews. Data analysis was used descriptively by comparing tests on field material with interview data. The results obtained from data analysis are the difficulties faced by students when solving field material questions on Ring Algebra, namely difficulties in determining the reversal of each existing element and confusion when determining the initial steps in working on the tests that have been given.